Blue light at night acutely impairs glucose tolerance and increases sugar intake in the diurnal rodent Arvicanthis ansorgei in a sex‐dependent manner. Issue 20 (23rd October 2019) - Masís‐Vargas, Anayanci; Hicks, David; Kalsbeek, Andries; Mendoza, Jorge
Abstract: In our modern society, the exposure to light at night (LAN) has increased considerably, which may impact human health negatively. Especially exposure to light at night containing short wavelength emissions ( 450–500 nm) can disrupt the normal function of the biological clock, altering sleep‐wake cycles and inducing metabolic changes. Recently, we reported that light at night acutely impairs glucose tolerance in nocturnal rats. However, light at night in nocturnal rodents coincides with their activity period, in contrast to artificial light at night exposure in humans. The aim of this study was to evaluate the acute effects of blue ( λ = 490 ± 20 nm) artificial light at night (bALAN) on glucose metabolism and food intake in both male and female diurnal Sudanian grass rats ( Arvicanthis ansorgei ) fed either regular chow or a free choice high‐fat high sucrose diet (HFHS). In both chow and HFHS fed male Arvicanthis, 1‐hour of bALAN exposure induced a higher glucose response in the oral glucose tolerance test (OGTT) accompanied by a significant decrease in plasma insulin. Furthermore, in HFHS fed animals, bALAN induced an increase in sucrose intake during the dark phase in males but not in females. Additionally, 1‐h of bALAN increased the nonfasted glucose levels together with plasma corticosterone in female grass rats. These results provide new and further evidence for the deleterious effects of exposure to short wavelength emission‐containing artificial light at night on glucose metabolism in a diurnal rodent in a sex‐dependent manner. Abstract : Blue artificial light at night (bALAN) acutely reduces glucose tolerance in the male diurnal rodent Arvicanthis ansorgei, fed either a chow or a free choice high‐fat high‐sucrose diet. bALAN exposure increases sucrose consumption in male Arvicanthis . Therefore, acute effects of bALAN on glucose metabolism and food intake are sex‐dependent in the diurnal rodent Arvicanthis ansorgei .